Forced degradation studies of a new antileishmanial molecules using a stability-indicating RP-HPLC method (2015)
ABSTRACT: A stability indicating RP-HPLC method was developed and validated to study the forced stability of a quinoline-triclosan hybrid, a new agent (Quinoline-triclosan hybrid) for cutaneous Leishmaniasis treatment. The method was developed using a C18 column (250 mm x 4.6 mm, 5 μm) and acetonitrile-water mixture was used as mobile phase. System suitability parameters, linearity, precision and accuracy were determined in the method validation. Quinoline-triclosan hybrid was exposed to various levels of stress conditions including photolytic, oxidative and acid and basic hydrolytic stress. The percentage of degradation in each condition was determined by HPLC. The hybrid was stable at all tested stress conditions with the exception of exposure to light, which was the only factor capable of producing a significant degradation of the molecule. Therefore, it is necessary to protect this molecule from light during development of a dosage form.